2020
DOI: 10.3892/etm.2020.9237
|View full text |Cite
|
Sign up to set email alerts
|

Lithium chloride ameliorated spatial cognitive impairment through activating mTOR phosphorylation and inhibiting excessive autophagy in the repeated cerebral ischemia‑reperfusion mouse model

Abstract: Lithium has been previously demonstrated to alleviate cognitive impairment caused by neurodegenerative diseases and acute brain injuries; however, the specific mechanism remains elusive. In the present study, the C57BL/6 mouse model of spatial cognitive impairment induced by repeated cerebral ischemia-reperfusion was established. Morris water maze test was performed to evaluate the levels of spatial cognitive impairment. Nissl staining was used to observe any morphological alterations, whilst western blotting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
2
10
0
2
Order By: Relevance
“…The autophagic process can be activated by nutritional deprivation or other stressful conditions. Previous studies have revealed that autophagy is upregulated following cerebral I/R in diabetes ( 2 , 65 , 66 ). Autophagy is characterized by the formation of autophagosomes that can engulf cytosolic organelles.…”
Section: Discussionmentioning
confidence: 96%
“…The autophagic process can be activated by nutritional deprivation or other stressful conditions. Previous studies have revealed that autophagy is upregulated following cerebral I/R in diabetes ( 2 , 65 , 66 ). Autophagy is characterized by the formation of autophagosomes that can engulf cytosolic organelles.…”
Section: Discussionmentioning
confidence: 96%
“…10 Other studies have shown that lithium treatment is associated with antiapoptotic eff ects, 15,34,43,49,51,52 decreased expression of inflammatory markers, 31,42,43,45,50 reduced oxidative stress, 35,43,45 and activation of immunomediated responses involved in the restoration of blood-brain barrier integrity. 44,50 Finally, evidence of trophic responses is supported by the ability of lithium to upregulate the brain-derived neurotrophic factor production, 39,52,53 to promote neuronal differentiation, axonal plasticity, and endogenous neurogenesis, 14,28,42,45 as well as to stimulate poststroke angiogenesis. 53 According to the SYRCLE's tool, the overall assessment of the quality of animal studies included in the review was ranked as good, that is, low risk of bias in most domains; except for performance-and detection-blinding, where the risk of bias was observed in >50% of studies.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium chloride (LiCl, Sigma-Aldrich, USA) was dissolved in 0.9% NaCl, and both the M+L group and M+L+D group rats were then treated with LiCl twice a day at the dose of 2.0 mmol/kg for one consecutive week after MCAO operation according to formerly described [16]. The S group and M group rats simultaneously received equivalent volumes of normal saline injected.…”
Section: Drug Administrationmentioning
confidence: 99%